Eco-Cultural Narratives and Interactions Between YouTube Users in Digital Environmental Communication - Nurul Haniza; Khairul Syafuddin (UPT Publikasi Ilmiah UNISBA, 2026)
Environmental communication faces challenges where audiences have become tired of facing various rigid environmental conservation messages. This has the potential to cause audiences to reach the saturation point and lead them to ignore the main message of environmental communication. This study explores hybrid narrative strategies in National Geographic Indonesia (Nat Geo Indonesia) digital travel documentary videos. The gap in this research relates to the imbalance between the delivery of rigid environmental conservation messages and the needs of digital media audiences. The purpose of this study is to analyze human interest narratives and social network structures in content published by Nat Geo Indonesia entitled Eksotika Jalur Selatan Jawa. This study uses multimodal discourse analysis on video texts and Social Network Analysis (SNA) on video comments. The novelty of this research lies in the combination of analytical techniques used to analyze human interest narratives in digital conservation messages. The results of this study indicate that local figures play a significant role as emotional anchors. This becomes an attraction for audiences in understanding culturally-based environmental communication narratives. In addition, the SNA analysis reveals the formation of network structures that encourage the formation of various public narratives.